Indeks Kepuasan Masyarakat dalam Pelayanan Publik di Kantor Kelurahan Ratu Sima Kota Dumai - Shaliza, Fara; Lestari, Cici; Wihendri, Wihendri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study was motivated by public complaints regarding the untimely commencement of services and unclear information about service requirements at the Ratu Sima Urban Village Office. Therefore, this study aims to determine the Community Satisfaction Index (IKM) and the key factors influencing public satisfaction with public services at the Ratu Sima Urban Village Office in Dumai City. This research employs a quantitative method with a survey research design. The study sample consists of 100 respondents, selected using an incidental sampling technique. Data were collected through questionnaires, observations, and interviews. Data analysis was conducted using the IKM value based on PAN-RB Ministerial Regulation Number 14 of 2017, assessing nine service elements. The measurement utilized a Likert scale with four alternative perception value responses. The results indicate that the IKM score is 3.15, with an IKM conversion value of 78.75. Based on this IKM score, the service performance at the Ratu Sima Urban Village Office is categorized as Good, with a service quality rating of B. The key factors determining public satisfaction are the specification of service types with a score of 1,055, and the competency of service providers, with a score of 998.